MALE AND FEMALE STUDENTS’ APOLOGIZING SPEECH ACT IN ACADEMIC SETTING - Ernawati Ningsih (Journal of English Education Program (JEEP), 2015)
This research aims to describe on the use of apologizing speech act strategies between male and female students in academic setting. In this research the writer would like to propose a research question: What are apologizing strategies performances used by male and female students? To get the data, the writer then gives twenty questionnaires called Discourse Completion Test (DCT) to twenty students; consists of ten male and ten female. The writer takes twenty students from the third grade of Galuh University as the respondents. To interpret the data, the writer uses qualitative design particularly a cross-sectional design. The result of the research shows that the study reveals the most dominant apologizing strategy used by both of male and female are apologizing was done by an expression of apology IFID+EXPL strategy and an expression of apology IFID+EXPL+IFID strategy. From the overall findings, the writer argues that male and female participants almost use the same strategy to respond to the addressee in each situation. The difference between them is in the frequency of apologizing strategies used to respond to the addressee in each situation. In the other hand, their similarity is in the way they express their apology, by using apologizing strategy, or it can be said that both of them prefer to state the word apology for apologizing in responding to each situation.Key words: speech act, apologizing, gender.